Hepatotoxicity Risk Profile of Indonesian Due to Polymorphism of NAT2 and CYP2E1 in Isoniazid Metabolism - Setiyo Budi Santoso; Puji Umi Chabibah; Prasojo Pribadi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This article presents data on drug-induced liver injury events' risk profile due to NAT2 and CYP2E1 polymorphisms in isoniazid metabolism in Indonesian populations among various populations of several countries. The research took place through a review of the literature obtained from google scholar. The library search uses three variants of the keyword: (1)